Implementasi Pajak Pertambahan Nilai Di Indonesia: Suatu Studi Perbandingan Di Negara-Negara ASEAN-9 - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2020)
Indonesia was the first country in Southeast Asia to implement the Value Added Tax on April 1, 1985. This step was then followed by several other countries in Southeast Asia, particularly those who were members of the ASEAN community. However, there are also a number of ASEAN member countries that do not use the Value Added Tax system. In this paper, a comparative study will be carried out on the application of Value Added Tax in Indonesia, compared to other ASEAN member countries, specifically with 8 ASEAN member countries, namely the Philippines, Cambodia, Laos, Malaysia, Myanmar, Singapore, Thailand, and Vietnam which together with Indonesia hereinafter referred to as ASEAN-9. Comparisons are only made among the 9 ASEAN member countries, and not the whole 11 ASEAN member countries, due to difficulties in gathering data from the other 2 ASEAN member countries. Overall implementation of Value Added Tax, or similar taxes in ASEAN-9 countries is good, and has many similarities in principle. This of course will provide many conveniences if it is desired to integrate the Value Added Tax system, or similar taxes into only one tax system that is uniformly applicable in ASEAN countries. From the results of comparative studies show that the implementation of Value Added Tax in Indonesia is still the best compared to 8 other ASEAN-9 countries, because it is in accordance with the basic principles of the Value Added Tax system. However, the Value Added Tax system implemented in Indonesia needs to be improved by removing the Value Added Tax collection rules by government treasurers, and certain business entities when making a purchase from a Taxable Entrepreneur.